Perancangan Interior Co-working Space dengan Fasilitas Day Care di Jakarta - Angelica Widjaja; Sherly de Yong; Lucky Basuki (Intra, 2019)
Along with the development of information and internet, many people feel bored working in the office and a lot of them choose to work flexibly. Flexibility in work place causes offices that have facilities such as co-working space are more in demand today. High economic needs made both parents work formally and or informally. The rush of both made it difficult for them to divide their time to work and also look after their children. Therefore, we need an interior coworking space with day care facilities as a solution to overcome the difficulties experienced by parents. The method used is design thinking method with stages including literature studies, field observation, analysis, schematics and 3D modeling. The design concept chosen is Fun and Socialize with the goal to increase productivity and relationships between users. This concept is applied in the use of colors and space’s zoning-grouping. This design project involves adult and child users in their activities supported by day care, lobby, locker, gaming area, meeting rooms, and staff-office. Colors used in the design are blue, orange, and yellow. Orange and yellow are used to balance the color blue which has calm psychological effect.